A Cultural Harmony between Islam and Local Tradition of Caram Seguguk in Rengas Payaraman, Ogan Ilir, South Sumatra - Mohammad Syawaludin (IAIN Surakarta, 2017)
The study attempts to look Islam as a religion which teaches various aspects of normative and humanism has undergone a process of acceptance and rejection in the society. Meanwhile, tradition as an identity of a particular community also has undergone an eclectic process in acquiring adaptation with the Islamic teachings. It proves that Islam is not merely understood as a doctrine but also as a result of the interaction of cultural values, norms, and morals representing in the forms of religious practices which tolerates the local values. The meeting between Islamic value and local tradition value are maintained. Then, they form Islamic narrated activities as a form of internalization of the teachings and community behaviors. Caram Seguguk tradition in South Sumatera is one of the results of the harmonization between Islam and local traditions in daily activities.